Understanding the self - Brawner, Dalisay G. (C & E Publishing Inc., 2018)
Understanding the Self is a modular textbook that examines the nature of the self and the various factors that affect the development of the self throughout one's life. It aims to make students better understand their own identity and address their goals to ultimately achieve their vision in life. Likewise, the book guides them in their study habits, in managing their emotions, and in taking care of their physical self, among others. It also presents tips for and guidelines on achieving success.
Module 1 Meet and Greet: My Home, My School 1 Module 2 Concept and Nature of Self: Who Am I? 4 Module 3 Physical Self: The Beautiful Me 15 Module 4 Intelligent Behaviors: Seeing My Natural Ability 26 Module 5 Emotional Self: Achieving My Emotional Competencies 32 Module 6 Social Self: Relating Harmoniously and Properly with Everyone 38 Module 7 Moral Self: Living with Purpose-Personal Value and Philosophy of Life 65 Module 8 Concept of Self: Understanding and Enhancing One's Self-image 78 Module 9 Responsible Self: My Commitment to Lifelong Growth 92 Module 10 Assessing for Self-improvement: Directing My Destiny 110 Module 11 The Best of Me: Outstanding Awards Day 124
Keywords: Psychology ; Human behavior